Nanoparticle Ripening : A Versatile Approach for the Size and Shape Control of Metallic Iron Nanoparticles. Issue 3 (21st March 2019) - Lacroix, Lise‐Marie; Meffre, Anca; Gatel, Christophe; Fazzini, Pier‐Francesco; Lachaize, Sébastien; Respaud, Marc; Chaudret, Bruno
Abstract: A novel approach for the synthesis of Fe(0) nanoparticles (NPs) with tunable sizes and shapes is reported. Ultrasmall Fe(0) NPs were reacted under mild conditions in the presence of a mixture of palmitic acid and amine ligands. These NPs acted not only as preformed seeds but also as an internal iron(II) source that was produced by the partial dissolution of the NPs by the acid. This fairly simple approach allows the strict separation of the nucleation and the growth steps. By changing the acid concentration, a fine tuning of the relative ratio between the remaining Fe(0) seeds and the iron(II) reservoir was achieved, giving access to both size (from 7 to 20 nm) and shape (spheres, cubes or stars) control. The partial dissolution of the ultrasmall Fe(0) NPs into iron(II) source and the successive growth was further studied by using combined TEM and Mössbauer spectroscopy. The successive corrosion, coalescence, and ripening observed could be understood in the framework of an environment‐dependent growth model. Abstract : Ripe fruits : Ultrathin Fe(0) nanoparticles can be used as an iron source for the size and shape control of metallic NPs in a nanoparticle ripening process. By adjusting the atmosphere, isotropic growth or oriented attachment can be selectively favored. The key role played by hydrogen gas in the final faceting was demonstrated, and leads to highly crystalline Fe nanostars or nanocubes.